Effect of Glucose Metabolic State Transition on Progression from Stage A to Stage C Heart Failure - Yin M; Xu X; Li J; Sun Y; Zhen Y; Wu S; Fang H (Diabetes, Metabolic Syndrome and Obesity, 2025)
Mingjie Yin,1 Xiaoyu Xu,2 Jie Li,1 Yanan Sun,3 Yanfeng Zhen,3 Shouling Wu,4 Hui Fang1,3 1Department of Internal Medicine, Hebei Medical University, Shijiazhuang, Hebei, People’s Republic of China; 2Training Base, Tangshan Gongren Hospital, Tangshan, Hebei, People’s Republic of China; 3Second Department of Endocrinology and Metabolism, Tangshan Gongren Hospital, Tangshan, Hebei, People’s Republic of China; 4Department of Cardiology, Kailuan General Hospital, Tangshan, Hebei, People’s Republic of ChinaCorrespondence: Hui Fang, Department of Internal Medicine, Hebei Medical University, 361 Zhongshan East Road, Shijiazhuang, Hebei, 050000, People’s Republic of China, Tel +8613831581838, Email fanghui2818@126.comBackground: Heart failure (HF) constitutes a significant global health challenge. The interplay between the dynamics of glucose metabolic status transitions and the progression of HF has been minimally explored.Objective: We assessed the impact of shifts in glucose metabolic states on the progression from stage A to stage C HF.Methods: The Kailuan Study is a large-scale prospective cohort study. Based on data from the Kailuan Study, 41,110 stage A HF patients were included and stratified into 6 groups based on alterations in glucose metabolic status: stable normoglycemic, stable pre-diabetes, diabetes, normoglycemic progressing to pre-diabetes, pre-diabetes back to normoglycemic, and normoglycemic/pre-diabetes progressing to diabetes. Utilizing the Cox proportional hazards regression model, we calculated the hazard ratios (HR) and 95% confidence intervals (CI) associated with the transition to stage C HF among patients with stage A HF with different glucose metabolic state transitions.Results: Our findings indicated a notably elevated risk for the progression to stage C HF within the diabetic group relative to the stable normoglycemic group (HR, 1.87; 95% CI, 1.66 to 2.10). Additionally, an augmented risk for the progression to stage C HF was observed in the normoglycemic/pre-diabetic to diabetic group (HR, 1.38; 95% CI, 1.15 to 1.65).Conclusion: Both diabetes and normoglycemic/pre-diabetes progressing to diabetes are associated with heightened risks of progressing from stage A to stage C HF. Conversely, the re-establishment of normoglycemic in pre-diabetes is associated with preventing HF progression.Keywords: glucose metabolic state, diabetes, pre-diabetes, stage A heart failure, stage C heart failure